High blood pressure in pregnancy, DNA methylation, and later blood pressure in African American women enrolled in the InterGEN Study. Issue 3 (15th August 2020) - Barcelona, Veronica; Wang, Zeyuan; Crusto, Cindy; Hui, Qin; Sun, Yan V.; Taylor, Jacquelyn Y.
Abstract: Background: Few studies have examined the effects of high blood pressure (BP) in pregnancy, preeclampsia, or eclampsia on later BP, and the epigenetics of this phenomenon is similarly poorly understood, especially among African Americans. The purpose of this study was to examine the association between high BP in pregnancy, epigenomics, and later BP in African American women in the InterGEN Study (n = 250). Methods: In cross‐sectional analyses, regression and linear mixed‐effects models were employed to examine the effects of high BP in pregnancy on: (a) epigenetic associations (DNA methylation) and (b) BP 3‐5 years after birth. The 850K Illumina EPIC BeadChip was used for evaluating epigenome‐wide DNA methylation. High BP in pregnancy, preeclampsia, or eclampsia was self‐reported by women, and BP was measured 3‐5 years after birth, per JNC‐7 guidelines. DNA methylation and clinical BP were the main outcomes. Results: Mean age of enrolled women was 31.2 years, 21.8% were smokers, 58% had some college or higher education, 46.6% reported an annual income <15 000, and 13.6% reported high BP in pregnancy. After adjustment for obesity, smoking, and age, women with a history of high BP in pregnancy had significantly higher BP than those who did not report this complication (5.39 ± 2.4 mm Hg, P = .030). Epigenome‐wide analysis revealed no significant sites after multiple testing correction. Conclusions: We observed a small, but clinically significant, increase in BP in women who reported high BP in pregnancy 3‐5 years after that pregnancy. Future studies with larger sample sizes should examine epigenetic contributions to this finding.